1998
DOI: 10.1159/000016488
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Enamel and Cementum Fluoride Uptake from Three Fluoride–Containing Composites

Abstract: The incorporation of fluoride into restorations is desirable because of its cariostatic action. The purpose of this study was to determine fluoride release and fluoride uptake by enamel and cementum from three visible light–cured fluoride–containing composites. Seven circular discs of each composite were prepared and the amount of fluoride released into distilled water was determined at daily intervals for 14 days and then after 30, 60 and 90 days. The fluoride concentration in enamel and cementum was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
1
12
0
2
Order By: Relevance
“…These results were significantly higher than those in the control group. Kawai et al obtained the same results for another composite resin they investigated 7) . Our present study concurred with these previous results and found that fluoriderecharge from pit-and-fissure sealants and filling materials on the surface of teeth occurred within a short time and that their application to teeth increased acid resistance on the surface.…”
Section: Discussionsupporting
confidence: 56%
“…These results were significantly higher than those in the control group. Kawai et al obtained the same results for another composite resin they investigated 7) . Our present study concurred with these previous results and found that fluoriderecharge from pit-and-fissure sealants and filling materials on the surface of teeth occurred within a short time and that their application to teeth increased acid resistance on the surface.…”
Section: Discussionsupporting
confidence: 56%
“…10,12 At this critical pH value, human saliva is unable to be saturated with calcium and phosphate ions. 13 Therefore, it is reasonable to consider that the chemical process that focused on the development of new materials to be used in dentistry must take into account the possibility of extensive fluoride release, following reduction of the pH to lower than 5.5. Physiochemical surface components found to be involved with bacterial adhesion are surface charge (zeta potential), [14][15] hydrophobicity/hydrophilicity, [16][17] surface-free energy (SFE) 17 and surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…수복재에서 유리된 불소는 치면에 흡수되어 탈회에 대한 저항성을 증가시킨다 22) . 불소 유리에 관한 연구들이 유리 량 에 있어 유사한 결과를 보인 반면 4,11,12) , 흡수에 관한 연구결 과는 실험방법과 재료에 따라 그 결과가 다양하게 나타났 다 12,23,24,25) . 치면에 흡수되는 불소에 관한 연구에서 산부식법 23,26) , 편 광현미경 27,28) , 전자탐침 미량분석기법 (Electron Probe Micro-Analysis-EPMA) 27,29) , 미세경도 측정법 30,31,32) 등이 이용되었다.…”
unclassified
“…치면에 흡수되는 불소에 관한 연구에서 산부식법 23,26) , 편 광현미경 27,28) , 전자탐침 미량분석기법 (Electron Probe Micro-Analysis-EPMA) 27,29) , 미세경도 측정법 30,31,32) 등이 이용되었다. 이러한 방법 중 산부식법은 부식의 깊이를 조 절하기 곤란하고 25) , 산에 잘 견디는 혼성층이 존재하는 경우 불소 농도의 측정이 불가능하다 33) . 또한 편광현미경은 재광 화와 우식저항에 대한 실제적인 양상을 관찰할 수 있는 장 점을 가지고 있지만, 재발성 우식이 진행되는 치아와 수복물 계면에서 불소의 흡수를 측정하기가 곤란한 단점이 있다 28) .…”
unclassified